Managerial economics economic tools for today's decision makers - Keat, Paul G.; Young, Philip K.Y (Prentice-Hall series in economics, 2000)
Illustrating the theory of managerial economics with an integrated case on the soft drink industry, this text shows students how to solve real business problems by enabling them to apply economic principles to everyday business activity.